The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00221-004-2013-z
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of saccadic dysmetria following localized lesions in monkey superior colliculus

Abstract: Damage to the monkey superior colliculus (SC) produces deficits in the generation of saccadic eye movements. Recovery of the accuracy of saccades is rapid, but saccadic latency and peak velocity recover slowly or not at all. In the present experiments we revisited the issue of recovery of function following localized lesions of the SC using three methodological advances: implantation of wire recording electrodes into the SC for the duration of the experiment to ensure that we were recording from the same site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
0
14
0
2
Order By: Relevance
“…Saccade hypometria in PD subjects may be caused by an excitation of the substantia nigra pars reticulata (SNr), which, in turn, inhibits the SC that specifies the size and direction of a saccade [14]. Accordingly, saccadic hypometria is found in SC lesions in patients [15] but has not been confirmed as a persistent deficit in a recent animal SC lesion study [9]. By contrast, saccadic circuits downstream of the SC seemed to be spared because blink-saccade interaction in our subjects was normal, i.e., blinks physiologically decreased saccade velocity [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Saccade hypometria in PD subjects may be caused by an excitation of the substantia nigra pars reticulata (SNr), which, in turn, inhibits the SC that specifies the size and direction of a saccade [14]. Accordingly, saccadic hypometria is found in SC lesions in patients [15] but has not been confirmed as a persistent deficit in a recent animal SC lesion study [9]. By contrast, saccadic circuits downstream of the SC seemed to be spared because blink-saccade interaction in our subjects was normal, i.e., blinks physiologically decreased saccade velocity [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The previous neurophysiological studies have indicated that dopamine-modulated oculomotor neurons in the basal ganglia regulate saccades through the superior colliculus (Wurtz and Goldberg, 1972; Schiller et al, 1980; Hikosaka and Wurtz, 1983, 1985a,b; Lee et al, 1988; van Opstal and van Gisbergen, 1990; van Opstal et al, 1995; Kawagoe et al, 1998; Sato and Hikosaka, 2002; Soetedjo et al, 2002; Hanes et al, 2005; Matsumoto and Hikosaka, 2009; Yasuda et al, 2012). For example, the superior colliculus– which received direct inhibitory inputs from the basal ganglia– exhibited a pre-saccadic burst of activity with a peak discharge rate positively correlated with saccadic peak velocity (van Opstal and van Gisbergen, 1990; van Opstal et al, 1995; Soetedjo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Larger lesions (data not shown) produced hypometric saccades, such as observed after muscimol injections (Quaia et al 1998), because the total number of SC spikes failed to reach the threshold. We conjecture that this threshold is under adaptive control, which would account for the altered movement fields after short-term adaptation of saccades (Frens and Van Opstal 1998) and the rapid recovery of amplitude deficits after small electrolytic lesions of the SC (Hanes et al 2005).…”
Section: Effects Of Sc Lesionsmentioning
confidence: 96%
“…The notion that each SC spike adds a tiny site-specific displacement vector to the movement command implies that eye velocity is not only influenced by the cell firing rates and their anatomical connection strengths with the brain stem, but also by the number of recruited cells. Indeed, it has been shown that when a subset of the active cell population is reversibly inactivated, saccade velocity is consistently reduced Lee et al 1988;Quaia et al 1998) and that these velocity deficits persist in the case of irreversible lesions (Hanes et al 2005). saccade endpoints with (green) and without (blue) lesion.…”
Section: Effects Of Sc Lesionsmentioning
confidence: 99%